Formal and informal institutions under codecision: Continuous constitution building in Europe - Henry Farrell; Adrienne Héritier (Max-Planck-Projektgruppe Recht der Gemeinschaftsgüter, 2002)
Current approaches examining the effect of institutions on policy processes have difficulty in explaining the results of the legislative process of codecision between European Parliament and Council within the European Union. The formal Treaty changes which gave rise to codecision have in turn given rise to a plethora of informal institutions, in a process which is difficult to understand using dominant modes of analysis. This article provides a framework for analyzing the relationship between formal and informal institutions, showing how the two may be recur-sively related. Formal institutional change at a particular moment in time may give rise to infor-mal institutions, which in turn may affect the negotiation of future formal institutions. The article applies this framework to the codecision process, showing how the codecision procedure has led to the creation of informal institutions and modes of decision making, which in turn have af-fected subsequent Treaty negotiations. Through strategic use of the relationship between formal and informal institutions, Parliament has been successful in advancing its interests over time, and increasing its role in the legislative process.
Keywords: 330